Ответы и объяснения

  • Опыт
  • Ведущий Модератор
2014-02-15T15:41:59+04:00
Lg3*(x+1)=t
3+2/t=2t
2t-2/t-3=0
2t^2-3t-2=0
t=1/4(3+-sqrt(9+16))=1/4(3+-5)
t1=-1/2
t2=2
x+1=3^2=9
x=8
x+1=3^(-1/2)
x=√3/3-1
Лучший Ответ!
  • fasalv
  • главный мозг
2014-02-15T15:46:38+04:00
3+2log_{x+1}3=2log_3(x+1)\\
2(log_3(x+1)-\frac{1}{log_3(x+1)})-3=0\\
(t=log_3(x+1))\\
2(t-1/t)-3=0\\
 \frac{2t^2-3t-2}{t} =0=>\\
t\neq0;\\
2t^2-3t-2=0\\t= \frac{3^+_-\sqrt{9+16}}{4} =\frac{3^+_-5}{4}\\
t=2=>log_3(x+1)=2;\\x+1=3^2;\\x=8\\\\t=-1/2=>log_3(x+1)=-1/2;\\x+1= \frac{1}{\sqrt3} ;\\x=\frac{1}{\sqrt3}-1
Комментарий удален
Было ограничение только на t
Все переходы тождественны
Комментарий удален